Learning organizations: a case study of changes in gender equality in decision-making bodies - Carvalho, T. (2021)
Despite the general legal and social environments in Europe and in Portugal being positive to the institutionalisation of equal opportunities in Higher Education Institutions (HEI), gender inequality seems to persist in stereotyped perceptions embedded within organisational cultures. The European Union (EU) has been developing several programmes to fund the promotion of Gender Equality Plans (GEP) in HEIs in the European context. It is encouraging to find that in some specific cases the implementation of these progresses has positive results. This is the case of the institution studied here, which committed to equality beyond rhetoric. The paper reports on a case study of best practices in promoting gender equality in decisionmaking bodies at the middle-management level in the University of Aveiro, in Portugal. Based on an international H2020 funded research project, the University of Aveiro has implemented GEPs resulting in an increase in the number of women in decision-making bodies. This paper explains the process of cultural change in general, as well as the rector’s team attitudes in particular to promote progress in the pursuit of gender equality in decision-making bodies. When the project started, women constituted only 5% of members in these middle management bodies (i.e. Deans of both university departments and polytechnic schools). One year after the implementation of the project, this percentage increased to 20%. The paper details the several steps taken to reach this result. First, the problem was identified based on a quantitative analysis of the gender composition of decision-making bodies at UA; then, the process through which members access these bodies was also analysed. In a second stage of the project, the rector was informed and instigated to more proactive in increasing women’s representativeness in the following elections. Without changing the regulations, it was possible to develop informal strategies. These are related with the identification of women with competencies to perform the job and with personal empowerment for them to appoint themselves for the position. Although progresses have been made, it is important to acknowledge that these initiatives are not enough to promote structural changes and more needs to be done to accelerate the pace of progress as well as to change institutional practices and individual mentalities.